Desenvolvimento de competências de inovação para mulheres de TOP Management Teams Positions - Silva, Eliane Beatriz Weide da (Universidade do Vale do Rio dos Sinos, 2023)
This dissertation presents a study on innovation skills for women who lead top teams, taking into account the low participation of women in the field of innovation work, especially with regard to the occupation of decision-making spaces. The literature already points to evidence as to the causes of this low participation due to sociocultural factors and low adherence to exact sciences courses that, consequently, generate a natural reflection in the field of work. However, studies that aim to understand the reason for their permanence in these areas are still incipient, despite the difficulties encountered, as well as trying to answer the research question: How to develop women’s innovation skills for top management teams positions? Thus, this qualitative approach study was carried out through interviews based on a semi-structured script among ten women, with already consolidated and prominent careers within the innovation area. The selection of the interviewees was done through the snowball method where each interviewee indicates a possible candidate. These women are part of teams in technology park companies in the metropolitan region of Porto Alegre, Rio Grande do Sul, such as Tecnopuc, Tecnosinos and Feevale Techpark. With a focus on contributing to the exploration of the theme, understanding how to develop innovation skills from an analysis of each trajectory, mapping the convergences, challenges and disruptive examples that led them to the success of their careers.
Keywords: Competências; Ecossistemas; Inovação; Empreendedorismo; Mulher; Skills; Ecosystems; Innovation; Entrepreneurship; Woman; ACCNPQ::Ciências Sociais Aplicadas::Administração